Functional testing of a human PBX3 variant in zebrafish reveals a potential modifier role in congenital heart defects - Gist H. Farr; Kimia Imani; Darren Pouv; Lisa Maves (The Company of Biologists, 2018)
Whole-genome and exome sequencing efforts are increasingly identifying candidate genetic variants associated with human disease. However, predicting and testing the pathogenicity of a genetic variant remains challenging. Genome editing allows for the rigorous functional testing of human genetic variants in animal models. Congenital heart defects (CHDs) are a prominent example of a human disorder with complex genetics. An inherited sequence variant in the human PBX3 gene (PBX3 p.A136V) has previously been shown to be enriched in a CHD patient cohort, indicating that the PBX3 p.A136V variant could be a modifier allele for CHDs. Pbx genes encode three-amino-acid loop extension (TALE)-class homeodomain-containing DNA-binding proteins with diverse roles in development and disease, and are required for heart development in mouse and zebrafish. Here, we used CRISPR-Cas9 genome editing to directly test whether this Pbx gene variant acts as a genetic modifier in zebrafish heart development. We used a single-stranded oligodeoxynucleotide to precisely introduce the human PBX3 p.A136V variant in the homologous zebrafish pbx4 gene (pbx4 p.A131V). We observed that zebrafish that are homozygous for pbx4 p.A131V are viable as adults. However, the pbx4 p.A131V variant enhances the embryonic cardiac morphogenesis phenotype caused by loss of the known cardiac specification factor, Hand2. Our study is the first example of using precision genome editing in zebrafish to demonstrate a function for a human disease-associated single nucleotide variant of unknown significance. Our work underscores the importance of testing the roles of inherited variants, not just de novo variants, as genetic modifiers of CHDs. Our study provides a novel approach toward advancing our understanding of the complex genetics of CHDs.